COMPARATIVE STUDY OF FIRM PERFORMANCE: EMS ADOPTER AND NON-ADOPTER FIRMS TO ACHIEVE SUSTAINABLE BUSINESS GOALS - Muhammad Raees Ashraf; Dr. Kausar Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
The paper titled "Comparative Study of Firm Performance: This paper titled "EMS Adopter and Non-Adopter Firms to Achieve Sustainable Business Goals" analyses the impact of EMS on organisational performance, thereby measuring firms’ financial, environmental and competitive performance. Hence, the research results lead to the conclusion that EMS adoption has a positive effect on environmental performance and can act as a source of competitive advantage by enhancing stakeholders’ relations and market positioning. Nonetheless, while EMS can cost some firms dearly initially, and they may struggle to implement it to the best effect, others reap handsome profits and the rewards from it in the long haul; moreover, the regulatory framework affects EMS, either positively or negatively. Firms from the environments that are keen on environmental measures perform better due to compliance pressure. However, other researchers have suggested that it is possible to enhance the advantages of EMS and the efficiency of various operations across the organization by integrating the management system with other systems like quality management and occupational health and safety systems. This type of analysis has certain weaknesses, which should be taken into consideration, including: Non-availability of impartial data as most of the data collected here are self-reported, and the fact that the regulatory environments may differ across territories. Additionally, it would also be useful to extend the analysis into the successful dual employment of EMS with other sustainable initiatives. This research also has prospects in developing a clearer perception of EMS capabilities in supporting sustainable business strategies and methods that can prompt the identification of the best approaches for applying EMS in specific contexts. Therefore, its conclusions are useful for business and policy strategies to support positive change and achieve permanent economic and environmental gains. Thus, by having all the pros and cons associated with the EMS provided here, companies are in a better position in planning their implementation of EMS and the subsequent results that would be attained. Leadership policymakers can also use these findings to develop sound regulatory policies for the spread of EMS and the encourage sustainability within the business organizations.